Μελέτη της επίδρασης των προκατεργασιών και των συνθηκών ξήρανσης στα ποιοτικά χαρακτηριστικά του δυόσμου (Mentha viridis) - Παράσχου, Αναστασία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Dry spearmint (Mentha viridis) is a popular aromatic plant used as an ingredient in the food industry, as a part of flavorings in cooking and consumed in the form of a decoction. It differs greatly from the fresh, as the drying method and the conditions applied to the processing determine to a great extent its quality. The drying process has a significant influence on quality characteristics as well as bioactive content of dried spearmint. Its economic value could be further increased if the drying process is applied in a way that ensures the production of high quality products and uniformity. The purpose of this study was to optimize drying process for the production of dry product of high quality. In particular, the effects of four pre-treatments (blanching with temperature 98ᵒC, blanching and immersing in a sulfite solution, immersion in citric acid solution, application of ultrasound irradiation) in combination with three air-temperatures (40 ° C, 50 ° C and 60 ° C) on the quality of dry spearmint were studied. The quality of final products was expressed with chromatic indicators, chlorophyll α and β contents, browning potential, phenolic composition and antioxidant capacity, decoction production potential and organoleptic characteristics (appearance, color, and aroma). Taking into consideration that consumers prefer dried produce that retains the characteristics of fresh material, the use of the immersion in citric acid solution and the air-drying at 40°C is recommended. In particular, the immersion in citric acid solution as a pre-treatment produces dry spearmint with higher content of chlorophyll a, total phenolics, hydroxycinnamates, flavones and antioxidant capacity among studied pre-treatments. On the other hand, the use of blanching as a pre-treatment helps to retain a bright green color, but the volume of dry spearmint is decreased dramatically and it smells like boiled grass.
Keywords: Drying; Air-temperature; Citric acid; Blanching; Sulfite; Ultrasound irradiation; Spearmint; Ξήρανση; Θερμοκρασία; Κιτρικό οξύ; Ζεμάτισμα; Θειώδη; Υπέρηχοι; Δυόσμος